ANALISIS PERAN KUALITAS PELAYANAN TERHADAP MINAT NASABAH DALAM MENABUNG DI PT BANK SYARIAH INDONESIA.TBK KC BINJAI - Deri Kuniawan; Muhammad Lathief Ilhamy Nasution (Jurnal Publikasi Manajemen Informatika, 2025)
This study aims to analyze the role of service quality on customer interest in saving at PT Bank Syariah Indonesia Tbk KC Binjai. A qualitative method was used with in-depth interviews with operational staff. The results showed that service quality, especially staff friendliness, service speed, and ease of digital access, significantly influenced saving interest. Challenges include queue management and technology education. Recommendations include improving staff competence, optimizing the digital queue system, and intensive technology education. This research provides practical insights for BSI KC Binjai to improve service quality and competitiveness in the Islamic banking market. Service quality plays an important role in attracting customers' interest in saving at PT Bank Syariah Indonesia Tbk KC Binjai, as well as challenges such as long queues and low technology adoption.